The Study of Safety Factors In the Production of Red Wine - Gulmira Irgasheva Rahimjonovna; Ostanaqulov Gayrat Normengliyevich (International Journal on Integrated Education, 2022)
Currently, a lot of attention is paid to the qualitative characteristics of wines. Red wine is characterized by a rich complex phenolic complex and has a high antioxidant capacity, predetermined by the high content of phenolic and coloring substances. Almost all groups of wine substances are involved in redox reactions - carbohydrates, phenolic and nitrogenous substances, organic acids. The intensity of the passage of oxidative enzymatic processes depends on technological methods, creating conditions for the passage of secondary redox processes. Based on the results obtained, the technological canons of winemaking were adjusted, for example, when processing red grapes, additional measures are clearly needed to ensure antioxidant protection.